Unleashing the clinical power of T cells: CD19/CD3 bi-specific T cell engager (BiTE) antibody construct blinatumomab as a potential therapy - Zimmerman, Zachary; Maniar, Tapan; Nagorsen, Dirk (International immunology, 2015)
Multi-agent chemotherapy is the standard treatment for most B cell malignancies. Since chemotherapy can be associated with significant toxicity and since relapses resistant to chemotherapy often develop, new therapies are needed. Blinatumomab (AMG 103 or MT103) is a late-stage candidate in clinical development, which belongs to a novel class of antibody constructs termed bi-specific T cell engager antibodies. This antibody construct has dual specificity for CD19 and CD3 and can re-direct polyclonal cytotoxic T lymphocytes toward the tumor. This review focuses on the pre-clinical and clinical development of blinatumomab as a powerful new tool in the treatment of B cell malignancies.